2000
DOI: 10.1093/humrep/15.2.476
|View full text |Cite
|
Sign up to set email alerts
|

Counselling couples and donors for oocyte donation: the decision to use either known or anonymous oocytes

Abstract: In order to avoid a long waiting period, the Centre for Reproductive Medicine of the Free University of Brussels suggests that couples in need of donor oocytes search for a donor among family and friends. Recipient couples can choose between two types of donation: known donation, i.e. treatment with the oocytes of the donor recruited by the couple, or anonymous donation, i.e. an exchange of the donor recruited by the couple with a donor recruited by another couple in order to ensure anonymity between donor and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
2
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 31 publications
1
63
2
8
Order By: Relevance
“…Despite several reports that undecided parents voice more concern over how and when to tell the child (18,(28)(29), the undecided women in this study did not express this concern as influencing their decision. Because the women were early in pregnancy, concerns about telling the child may not be as paramount as when the child is actually present in the woman's everyday environment.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…Despite several reports that undecided parents voice more concern over how and when to tell the child (18,(28)(29), the undecided women in this study did not express this concern as influencing their decision. Because the women were early in pregnancy, concerns about telling the child may not be as paramount as when the child is actually present in the woman's everyday environment.…”
Section: Discussioncontrasting
confidence: 94%
“…Recipient individuals selecting non-disclosure have reportedly placed more emphasis on protecting the child from stigma and voiced concern that there is no compelling reason to tell (18)(19)28,33). Only one woman who participated in this study indicated she was not planning to tell her child.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A number of studies undertaken in various countries have explored parents' views regarding disclosure to their donor-conceived children of the means of their conception. To date, most of the study populations relating to oocyte donation have been recipients of anonymous donation whose children have been aged up to eight years (Pettee and Weckstein, 1993;Weil et al, 1994;Söderström-Anttila et al, 1998;Baetens et al, 2000;Hahn and CraftRosenberg, 2002;Greenfeld and Klock, 2004;Klock and Greenfeld, 2004;Golombok et al, 2004Murray et al, 2006;Mac Dougall et al, 2007;van Berkel et al, 2007;Laruelle et al, 2012), although one recent Finnish study has included parents of children aged up to 14 years (Söderström-Anttila et al, 2010). These studies have revealed intended disclosure rates of between 26 and 81%, although not all parents indicating an intention to disclose will necessarily do so Golombok et al, 2006;Murray et al, 2006;Mac Dougall et al, 2007;van Berkel et al, 2007), and only three studies have included longitudinal data tracking parental disclosure behaviour.…”
Section: Introductionmentioning
confidence: 99%